2016
DOI: 10.1017/jfm.2016.327
|View full text |Cite
|
Sign up to set email alerts
|

Long wave propagation and run-up in converging bays

Abstract: Analytical solutions are derived to describe two-dimensional wave evolution in converging bays. Three bay types of different cross-sections are studied: U-shaped, V-shaped and cusped bays. For these bays, the two-dimensional linear shallow water equations can be reduced to one-dimensional linear dispersive wave equations if the transverse flow acceleration inside them is assumed to be small. The derived solutions are characterized as the leading-order plane-wave solutions with higher-order corrections for two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…The latter means the presence of steep fronts (the gradient catastrophe) within the hyperbolic shallow-water equation framework. The Carrier-Greenspan transformation was further generalized for the case of waves in an inclined channel of an arbitrary variable cross section (Rybkin et al, 2014;Pedersen, 2016;Shimozono, 2016;Anderson et al, 2017;Raz et al, 2018). In a number of practical cases, its use proves to be more efficient than the direct numerical computation within the 2-D shallow-water equation framework (Harris et al, 2015(Harris et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The latter means the presence of steep fronts (the gradient catastrophe) within the hyperbolic shallow-water equation framework. The Carrier-Greenspan transformation was further generalized for the case of waves in an inclined channel of an arbitrary variable cross section (Rybkin et al, 2014;Pedersen, 2016;Shimozono, 2016;Anderson et al, 2017;Raz et al, 2018). In a number of practical cases, its use proves to be more efficient than the direct numerical computation within the 2-D shallow-water equation framework (Harris et al, 2015(Harris et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The most likely explanation may be wave refraction in the bay. Shimozono (2016) analytically examined long-wave propagation in converging bays and showed that waves with relatively short periods are significantly refracted during their propagation into bays. To investigate the wave refraction effect, Fig.…”
Section: Frequency-dependent Amplification Characteristics For the 20mentioning
confidence: 99%
“…Recall that the main assumption in using the 1‐D SWEs is that the incoming wave primarily propagates along the main axis of the bay. It has been shown that in symmetric U‐shaped bays the 2‐D effects are small if the wave length is sufficiently longer than the bay width (Anderson et al, ; Shimozono, ). Because of this, our first analysis of the FUNWAVE results will be to observe if the 2‐D effects are similarly small when the bays cross section is no longer symmetric.…”
Section: Validation Of the Csa Swes To Model Runup Of Long Wavesmentioning
confidence: 99%